2018
DOI: 10.1002/lipd.12126
|View full text |Cite
|
Sign up to set email alerts
|

Leucine, Palmitate, or Leucine/Palmitate Cotreatment Enhances Myotube Lipid Content and Oxidative Preference

Abstract: Branched‐chain amino acids (BCAA) such as leucine stimulate favorable metabolic processes involved in lean tissue preservation and skeletal muscle metabolism. However, higher levels of circulating BCAA correlate with severity of metabolic disease (including diabetes/insulin resistance), and may result from dysregulated BCAA catabolism. Past observations have demonstrated potential interaction between BCAA and dietary fat; however, much of this relationship remains underexplored. This study investigated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…Previous in vivo research from our laboratory also showed increased expression of markers such as FAS and PPAR␥ in skeletal muscle from obese Zucker rats fed with a high-protein diet containing a high amount of leucine (12). Moreover, treatment of C2C12 myotubes with palmitate and leucine reduced the effect of leucine on regulation of Tfam and PGC1␣ (19). Here, we report upregulation of mitochondrial biogenesis-related gene expression (e.g., PGC1␣, PPAR␥, NRF1, and Tfam) and mitochondrial content observed in palmitate-treated myotubes with leucine supple-mentation.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous in vivo research from our laboratory also showed increased expression of markers such as FAS and PPAR␥ in skeletal muscle from obese Zucker rats fed with a high-protein diet containing a high amount of leucine (12). Moreover, treatment of C2C12 myotubes with palmitate and leucine reduced the effect of leucine on regulation of Tfam and PGC1␣ (19). Here, we report upregulation of mitochondrial biogenesis-related gene expression (e.g., PGC1␣, PPAR␥, NRF1, and Tfam) and mitochondrial content observed in palmitate-treated myotubes with leucine supple-mentation.…”
Section: Discussionsupporting
confidence: 53%
“…Leucine is well known for activating the mTORC1 pathway in multiple cell types (16,19), leading to activation of the translation initiation factors, which can increase protein synthesis. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been great interest in the role of Leu in the metabolism of the adipose tissue [33]. It is important to emphasize that many in vitro and in vivo experiments have shown that Leu modulates lipid metabolism, mainly by inhibiting fat synthesis and decomposition, and increasing energy consumption [11,14,55]. There is growing evidence to suggest that the mitochondria may play a key role in modulating adipocyte lipid metabolism [56][57][58].…”
Section: Leu Modulates Lipid Metabolism Via Mitochondriamentioning
confidence: 99%
“…Aspartate a synthetic precursor of Lysine, Threonine and other amino acids as well as purine and pyrimidine based in vivo. It could be used as an adjutant in curing heart disease, liver disease and hypertension, and was effective in relieving fatigue (Hansen and Behrman, 2016); Serine had a wide range of medical applications, functioning as fat and fatty acid metabolism boosters or serving as normal immune function maintenance (Abbas, 2017); Leucine and its metabolites had regulatory effects on nutrient metabolism, neuroendocrine regulation, gene expression, signal transduction and immune function in vivo (Johnson et al, 2018). As an essential amino acid, Lysine can help drive human development, enhanced immune function, and improved the function of central nervous tissue (Passioura et al, 2019).…”
Section: Discussionmentioning
confidence: 99%